QUALITY OF DIUTED BOAR SEMEN USING PALMYRA FRUIT WATER WITH THE ADDITION OF VARIOUS CONCENTRATIONS OF EGG YOLK AND MORINGA LEAF EXTRACT - I Made Gede Raditya Darmayoga; Wayan Bebas; Luh Gde Sri Surya Heryani; I Gusti Ngurah Bagus Trilaksana; Desak Nyoman Dewi Indira Laksmi; I Wayan Sukernayasa (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Diluent is a substance used to maintain and protect spermatozoa during the storage process. Natural-based diluents are still rarely found, making it necessary to develop diluents derived from naturally available ingredients. This study aims to evaluate the effect of palmyra fruit water diluent with the addition of various concentrations of egg yolk and moringa leaf extract on the quality of boar semen. This study used one Landrace boar as the semen source, approximately 1.5 years old, in healthy condition. The study employed a Completely Randomized Design CRD with seven treatments: T0 as the control palmyra fruit water diluent only, T1 palmyra fruit water + 10% egg yolk + 5% moringa leaf extract, T2 palmyra fruit water + 10% egg yolk + 10% moringa leaf extract, T3 palmyra fruit water + 10% egg yolk + 15% moringa leaf extract, T4 palmyra fruit water + 20% egg yolk + 5% moringa leaf extract, T5 palmyra fruit water + 20% egg yolk + 10% moringa leaf extract, and T6 palmyra fruit water + 20% egg yolk + 15% moringa leaf extract. The semen was stored at a temperature of approximately 15-20°C for 48 hours. The observed semen quality parameters included motility, viability, and spermatozoa abnormalities, with each treatment repeated four times. The obtained data were analysed using ANOVA, followed by Duncan's test if significant differences were found. The results of Duncan's test indicated that the T6 treatment produced the best semen quality compared to other treatments, with motility at 59.50±1.291%, viability at 59.25±1.708%, and abnormalities at 7.25±0.500%. It can be concluded that the diluent formulation that resulted in the best spermatozoa quality after 48 hours of storage was treatment T6, composed of palmyra fruit water + 20% egg yolk + 15% moringa leaf extract. Further research is needed to determine the fertility potential of Landrace boar semen diluted with palmyra fruit water extender with the addition of various concentrations of egg yolk and moringa leaf extract to evaluate the effectiveness of the extender in an artificial insemination program.